Urban gulls show similar thermographic and behavioral responses to human shouting and conspecific alarm calls - Di Giovanni, Julien; Fawcett, Tim W.; Templeton, Christopher N.; Raghav, Shubhi; Boogert, Neeltje J. (Frontiers in Ecology and Evolution, 2022)
Rapid population growth and the urbanization of modern environments are markedly increasing human-wildlife conflict. Wild animals in urban landscapes can benefit from exploiting human resources, but are also exposed to increased risk of human-caused injury, which should favor the ability to perceive and respond to human cues. Although it is well known that domesticated animals use human cues that may indicate threats, less is known about wild animals living in urban environments. Herring gulls (Larus argentatus) in urban landscapes have adapted kleptoparasitic behaviors to obtain human food, often resulting in negative interactions with humans. Here we quantified both the behavioral and physiological responses of free-living urban herring gulls to human shouting. We presented urban gulls with a fake human food item and played back recordings of either a man shouting, a natural stressor (i.e. conspecific alarm call), or a neutral stimulus (i.e. robin song). We recorded behavioral responses and used non-invasive infrared thermography to measure eye-region surface temperature changes associated with the avian physiological stress response. We found that gulls exposed to shouting and to conspecific alarm calls showed similar changes in behavior (indicating high levels of vigilance) and eye-region surface temperature (indicating physiological stress). Both responses were significantly stronger than the responses to robin song. Additionally, the behavioral and physiological responses were positively correlated across individuals. Our results demonstrate that urban-dwelling gulls respond to human shouting and conspecific alarm calls in a similar way, and suggest that infrared thermography is a viable technique to monitor stress responses in free-living birds.